Bioelectrical phase angle, muscle damage markers and inflammatory response after a competitive match in professional soccer players - Moya-Amaya, H.; Molina-López, A.; Berralaguilar, A. J.; Rojano-Ortega, D.; Berral-De La Rosa, C. J.; Berral-De La Rosa, F. J. (Polish Journal of Sport and Tourism, 2021)
Introduction. The purposes of this study were 1) to evaluate changes from baseline levels in bioelectrical phase angle (PhA) and markers of muscle damage and inflammation in professional players 36 h after a soccer match, and 2) to analyze the relationships between PhA and markers of muscle damage and inflammation in order to investigate if PhA might be a useful parameter to monitor recovery.